Antimicrobial efficacy of cordless sonic or ultrasonic devices on Enterococcus faecalis‐infected root canals. Issue 4 (11th July 2019) - Pedullà, Eugenio; Genovese, Carlo; Messina, Riccardo; La Rosa, Giusy R. M.; Corsentino, Giacomo; Rapisarda, Silvia; Arias‐Moliz, Maria T.; Tempera, Gianna; Grandini, Simone
Abstract: Aim: The aim of the present study was to evaluate the immediate and residual antimicrobial activity of cordless sonic or ultrasonic devices on Enterococcus faecalis ( E faecalis )‐infected teeth. Methods: A total of 140 single‐rooted extracted teeth with E faecalis were grouped as follows (N = 15): conventional syringe irrigation with 3% sodium hypochlorite activated by ultrasonic device (group 1) or cordless ultrasonic device (group 2), EndoActivator (group 3) or without activation (group 4), conventional syringe irrigation with sterile bi‐distilled water and ultrasonic device (group 5), EndoUltra (group 6), EndoActivator (group 7), or without activation (group 8). The remaining 20 teeth were used for positive and negative controls. Colony‐forming units (CFU) and turbidity were recorded from bacteriological samples taken before and after irrigation and after 24 hours of re‐incubation. Data were statistically analyzed using Student's t test, Mann‐Whitney test, Kruskal‐Wallis test, and Dunn's multiple comparison tests ( P < .05). Results: Groups 1 and 2 showed higher antimicrobial efficacy than groups 3 and 4 ( P < .05). No bacteria reduction was found in groups 5‐8 ( P > .05). After 24 hours, regrowth of bacteria was not significantly different for all groups ( P > .05). Conclusions: Ultrasound produced lower CFU and turbidity after treatment and after re‐incubation of 24 hours than sonic or no activation.